DAMPAK PERMAINAN TERHADAP KEMAMPUAN ATLETIK LARI SPRINT PADA SISWA SEKOLAH DASAR: STUDI SLR - Utami, Tri Setyo (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research aims to investigate the influence of games on the sprinting ability of elementary school students through a Systematic Literature Review (SLR). The SLR approach was employed to examine previously published studies related to how games impact sprint running skills in elementary school students, with a focus on literature from 2020 to 2024. This method was chosen for its ability to systematically compile and organize findings from multiple relevant sources. The data reviewed were drawn from scientific articles published in national journals, accessed via the Google Scholar platform. A total of five articles were analyzed. The findings indicate that various games, such as the traditional game of gobak sodor, play-based short-distance running lessons, cat and mouse games, and sprint-focused learning activities using a game approach, can effectively enhance students' sprint abilities. However, the recommendations derived from this study are primarily applicable to fourth and fifth-grade students, with limited insights into appropriate games for improving sprint abilities across all elementary school grade levels.